2021
DOI: 10.1101/2021.07.23.21261027
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patterns of adverse childhood experiences and associations with prenatal substance use and poor infant outcomes in a multi-country cohort of mothers: A Latent Class Analysis

Abstract: Aims This paper explores the number and characterization of latent classes of adverse childhood experiences across the Evidence for Better Lives Study cohort and investigates how the various typologies link to prenatal substance use (i.e., smoking, alcohol, and illicit drugs) and poor infant outcomes (i.e., infant prematurity and low birth weight). Participants and setting A total of 1,189 mother-infant dyads residing in eight diverse low- and middle-income countries (LMICs) were recruited. Methods Latent clas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Person-centred analyses, such as latent profile analyses, allow common exposure patterns to be identified among subgroups of participants [ 42 ]. Previous studies utilizing this method have shown how the method can provide illumination on adverse childhood experiences (e.g., [ 21 , 34 ],see [ 51 ] for review). For example, Hemady et al [ 34 ] conducted a latent profile analysis of adverse childhood experiences in a multi-country cohort and found that the sample could be divided into four classes (i.e., “ Highly Maltreated ”, “ Emotionally and Physically Abused with Intra-familial Violence Exposure ”, “ Emotionally Abused”, and “ Low Household Dysfunction and Abused ”) differing in their outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Person-centred analyses, such as latent profile analyses, allow common exposure patterns to be identified among subgroups of participants [ 42 ]. Previous studies utilizing this method have shown how the method can provide illumination on adverse childhood experiences (e.g., [ 21 , 34 ],see [ 51 ] for review). For example, Hemady et al [ 34 ] conducted a latent profile analysis of adverse childhood experiences in a multi-country cohort and found that the sample could be divided into four classes (i.e., “ Highly Maltreated ”, “ Emotionally and Physically Abused with Intra-familial Violence Exposure ”, “ Emotionally Abused”, and “ Low Household Dysfunction and Abused ”) differing in their outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies utilizing this method have shown how the method can provide illumination on adverse childhood experiences (e.g., [ 21 , 34 ],see [ 51 ] for review). For example, Hemady et al [ 34 ] conducted a latent profile analysis of adverse childhood experiences in a multi-country cohort and found that the sample could be divided into four classes (i.e., “ Highly Maltreated ”, “ Emotionally and Physically Abused with Intra-familial Violence Exposure ”, “ Emotionally Abused”, and “ Low Household Dysfunction and Abused ”) differing in their outcomes. While these previous studies demonstrate the value of the latent class approach to illuminating abuse profiles and their consequences, only a few (e.g., [ 48 , 62 ] have provided an in-depth exploration of different childhood psychological maltreatment profiles (i.e., psychological abuse, psychological neglect, and psychological non-support) specifically.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Dobson et al (2021) used a latent pro le analysis of adverse childhood experiences and explored adult mental health in community samples and found the samples could be divided in to four pro les (i.e., "Dysfunctional Family Environment", "Sexually Abused", "Emotionally Mistreated", and "No Mistreatment"). Another more recent study (Hemady et al, 2021) conducted a latent pro le analysis of adverse childhood experiences in a multi-country cohort and found that the sample could be divided in to four classes (i.e., "Highly Maltreated", "Emotionally and Physically Abused with Intra-familial Violence Exposure", "Emotionally Abused", and "Low Household Dysfunction and Abused") differing in their outcomes. While these previous studies demonstrate the value of the latent class approach to illuminating abuse pro les and their consequences, none have thus far provided an in-depth exploration of different childhood psychological maltreatment forms (i.e., psychological abuse, psychological neglect, and psychological non-support) speci cally.…”
Section: Introductionmentioning
confidence: 99%